Transposisi Kreatif Gerak Wayang Makidhipuh dalam Film Setan Jawa Karya Garin Nugroho - Dewi, Agustina Kusuma (LP2M ISBI Bandung, 2021)
Abstract: Garin Nugroho's ‘Setan Jawa’ is a performance film that carries a large narrative background to the story is the beginning of the 20th century in Java. With the accompaniment of live music by Rahayu Supanggah, the film was first released in 2016, and until 2020 a world tour is scheduled. 'Movement' becomes important in this film, which is a silent cross-disciplinary film, which combines dance and puppet shadows. The 'Movement' in the film ‘Setan Jawa’ gives a certain cultural meaning, that is Javanese culture, which arises through visual movement’ code, a creative transposition adapted from the wayang. Using a case study approach, supported by visual data analysis in the form of ‘Setan Jawa’ film documentation and referential data in the form of movement’ classifications in puppet shadows (Roger Long, 1979), this study produced findings that there were creative puppet movement transpositions made in the film ‘Setan Jawa’, i.e. Makidhipuh's movement. This finding reinforces the importance of adaptation and collaboration in the performing arts in the era of visual onslaught in order to maintain local culture. Keywords: film setan jawa, movement code, puppet movementAbstrak: ‘Setan Jawa’ karya Garin Nugroho merupakan film pertunjukan yang mengangkat narasi besar latar belakang cerita adalah awal abad ke-20 di Jawa. Dengan iringan musik live buatan Rahayu Supanggah, film ini pertama kali dirilis tahun 2016, dan hingga tahun 2020 dijadwalkan tur keliling dunia. ‘Gerak’ menjadi penting dalam film yang merupakan film bisu silang disiplin ini, yang diantaranya memadukan seni tari dan wayang. ‘Gerak’ pada film ‘Setan Jawa’ memberikan makna kultural tertentu, yaitu kultur Jawa, termunculkan melalui kode gerak visual, sebuah transposisi kreatif diadaptasi dari gerak wayang kulit. Menggunakan pendekatan studi kasus, didukung analisis data visual berupa dokumentasi Film ‘Setan Jawa’ dan data referensial berupa klasifikasi gerak pada wayang (Roger Long, 1979), penelitian ini menghasilkan temuan bahwa ada transposisi gerak wayang yang dilakukan secara kreatif pada film ‘Setan Jawa’, salah satunya, gerak Makidhipuh. Temuan ini menguatkan pentingnya adaptasi dan kolaborasi dalam seni pertunjukan di era gempuran visual agar dapat memertahankan budaya lokal.Kata kunci: film setan jawa, kode gerak, gerak wayang